Analysis of Sosio - Juridical Participation of Sota Village Government in Increasing Income of Marind Kanum Indigenous People in Sota Merauke Village - Yuldiana Zesa Azis; Nasri Wijaya (Faculty of Law, Musamus University, 2019)
The Merauke regency area has a village level government, one of which is Sota village which is one of the villages located on the border of the State of Indonesia and Papua New Gunea. One of the indigenous people who inhabit the Sota village area is the Marind Kanum Tribe. Administratively for community empowerment to increase income is one of the roles of the village government, especially for the indigenous people, the increase in income still needs to be increased Because the average income of the local community is still relatively low, therefore support from various parties including local government through the relevant agencies. The purpose of this study was to find out how the role and government of the Sota village in increasing the income of the indigenous people of Marind Kanum and to determine the extent to which the laws and regulations governed that. The results of this study indicate that the participation of the village government by assigning tasks to village officials is to provide training and aquipment assistance for business to local communities and transmigration which in this case is in accordance with Law number 6 of 2014 concerning Village Government.